Evaluation of a Wireless Data Transmission Using a Low-Cost Commercial-off-the-Shelf Wi-Fi Router Applied to Dynamic Tests - Mateus Rodrigues Rocha; Anderson Govertz; Rogerio Pirk; Edilson Alexandre Camargo (Journal of Aerospace Technology and Management)
The use of non-intrusive instrumentation has been growing in different scenarios in the industry. In the aerospace field, non-intrusive or hybrid instrumentation approaches have demonstrated robustness and viability, presenting significant advantages such as mass reduction of space vehicles, flexibility, and reduction of instrumentation lead time. This work presents a brief overview of a hybrid instrumentation system, in which the Wi-Fi standard communication protocol is highlighted. As a case study, the experimental structural modal analysis technique was adopted to show the technical advantages of using this promising data acquisition (DAq) system. To achieve this, test data were acquired using the traditional wired method between sensors, DAq, and the computer, as well as a wireless transmission protocol, via Wi-Fi, between the DAq and the computer. The comparisons of the results of the modal analysis experiments showed good agreement, indicating the Wi-Fi communication protocol is suitable and reliable for the tested scenario.